2017
DOI: 10.1080/08958378.2016.1277571
|View full text |Cite
|
Sign up to set email alerts
|

Adverse respiratory effects in rats following inhalation exposure to ammonia: respiratory dynamics and histopathology

Abstract: Acute respiratory dynamics and histopathology of the lungs and trachea following inhaled exposure to ammonia were investigated. Respiratory dynamic parameters were collected from male Sprague-Dawley rats (300-350 g) during (20 min) and 24 h (10 min) after inhalation exposure for 20 min to 9000, 20,000, and 23,000 ppm of ammonia in a head-only exposure system. Body weight loss, analysis of blood cells, and lungs and trachea histopathology were assessed 1, 3, and 24 h following inhalation exposure to 20,000 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…At the low dose, the effects of PH 3 inhalation on respiratory dynamics and clinical observations were markedly different from those observed at all other exposure doses, with only slight increases in MV n and no discernible signs and symptoms observed. However, the increase in net respiration was consistently observed at all PH 3 exposure doses, and this contrasts sharply with previous work using real-time plethysmography to examine the respiratory patterns of rats during exposure to chemical agents from different toxidromes, including diisopropylfluorophosphate (DFP) (Wong, Perkins, Santos, Rodriguez, Murphy and Sciuto 2013), soman (Perkins, Wong, Rodriguez, et al 2015), and ammonia (Perkins et al 2017), which found that agent exposure typically induced net decreases in respiration over the course of exposure. However, for PH 3 , the elevation of MV is primarily driven by increases in TV at the moderate and high doses, but by increases in f in the low-dose group.…”
Section: Discussioncontrasting
confidence: 98%
“…At the low dose, the effects of PH 3 inhalation on respiratory dynamics and clinical observations were markedly different from those observed at all other exposure doses, with only slight increases in MV n and no discernible signs and symptoms observed. However, the increase in net respiration was consistently observed at all PH 3 exposure doses, and this contrasts sharply with previous work using real-time plethysmography to examine the respiratory patterns of rats during exposure to chemical agents from different toxidromes, including diisopropylfluorophosphate (DFP) (Wong, Perkins, Santos, Rodriguez, Murphy and Sciuto 2013), soman (Perkins, Wong, Rodriguez, et al 2015), and ammonia (Perkins et al 2017), which found that agent exposure typically induced net decreases in respiration over the course of exposure. However, for PH 3 , the elevation of MV is primarily driven by increases in TV at the moderate and high doses, but by increases in f in the low-dose group.…”
Section: Discussioncontrasting
confidence: 98%
“…This respiratory pattern differs from that commonly observed for respiratory irritants and various chem-ical agents, where animals exhibit MV reductions, likely in an attempt to lessen exposure or as a side effect of direct damages caused by caustic or corrosive chemicals. [35][36][37] Interestingly, animals exposed to PH 3 also showed signs and symptoms consistent with hypoxia (Table 1; e.g., lethargy) despite the absence of reduced ventilation. The apparent disparity between physiology and behavior suggests that oxygen transport or oxygen bioavailability may be hindered.…”
Section: Discussionmentioning
confidence: 94%
“…However, animal monitoring was terminated at 8 h after MIC exposure and coagulation within the airways was not investigated during that study. Given the propensity of TICs to induce leakage of blood plasma, fibrinogen, and other clotting factors into the airways, [22][23][24][25][26] we hypothesized that extravascular coagulation in airways resulted from MIC inhalation. Furthermore, we supposed that the fibrinolytic agent tissue plasminogen activator (tPA) could mitigate airway obstruction and mortality after MIC inhalation.…”
Section: Introductionmentioning
confidence: 99%